Case Report: A Promising Treatment Strategy for Noninfectious Uveitis - Liu, Xiao-Bao; Tang, Lu-Shi; Chen, Jing-Wen; Lin, Chang-Song; Liu, Qiu-Hong; Xu, Qiang (Frontiers in Pharmacology, 2022)
Background: Uveitis refers to inflammation in the uvea, retina, retinal blood vessels, and vitreous, which can lead to irreversible eye damage and permanent vision loss. Glucocorticoid drugs are the first-line treatment, but side effects, such as obesity and hyperglycemia, can occur. Therefore, biologics have become a new treatment choice. Case Presentation: A 18-year-old girl developed eye pain and was diagnosed with binocular uveitis. Prednisone 50 mg was administered once a day, and the redness and pain in both eyes improved. Later, the prednisone dose was gradually reduced, and treatment was discontinued 3 years ago. Two years ago, the patient's condition relapsed, with both eyes becoming red and painful. She was administered prednisone 20 mg once daily and adalimumab. Visual acuity in both eyes continued to progressively decrease, accompanied by cataracts. At the same time, the patient experienced complications, including obesity and hyperglycemia. Subsequently, a new treatment regimen, oral prednisone 20 mg once a day, tofacitinib 5 mg twice a day, and methotrexate 10 mg once a week, as well as the use of insulin to control blood sugar, was initiated. One month later, the patient's redness and eye pain eased, and her vision gradually improved. The dosage of prednisone was gradually reduced to 5 mg once daily. At the same time, her blood sugar returned to normal, and insulin was stopped. Outcomes: The patient was treated with tofacitinib for ten months. Subsequently, her best-corrected visual acuity of the right eye rose from 0.06 to 0.075, and the best-corrected visual acuity of the left eye rose from CF/30 cm to CF/100 cm. Redness and eye pain were relieved, her glucocorticoid consumption reduced from 15 mg to 2.5 mg, and her blood sugar gradually normalized. Conclusion: This case study shows that tofacitinib relieves ocular inflammation in patients with uveitis and improves eyesight. We believe that JAK inhibitors could be another treatment option for noninfectious uveitis in patients who do not respond to conventional anti-TNF-α inhibitors (such as adalimumab).